واقع العنف ضد المرأة في محافظة السليمانية - مصطفى, د.عالية فرج; محمد, د.نياز عزالدين (Sulaimani Journal for Humanities, 2023)
Violence against women is considered one of the social phenomena that have received international attention by various agencies United Nations, civil society organizations, and international organizations. It becomes the focus of the research and statistical centers in the university and governmental and has made violence against women a vital issue related to the reality of life within local communities on the one hand, and an indicator by which the levels of social life are measured on the other hand. The research focuses on analyzing the annual statistics issued by the Ministry of Interior in the Kurdistan Region from 2014 to 2021 related to violence against women focusing on the patterns of violence: murder, suicide, burning, self-immolation, sexual harassment and complaints, as well as the reason of the continuation of patterns of violence from a perspective of research sample units. In terms of research methodology, the researchers adopted the analytical descriptive approach to analyze the statistics and the purposeful sampling, which included four directors of battered women's shelters, two activists in the field of civil society, and five administrators from the administrative body of the directorates of confronting violence against women in Sulaymaniyah Governorate. The two researchers applied a semi-structural interview to collect information from the research sample units. Among the results reached by the researchers: There is a level of civic awareness among the citizens of Sulaymaniyah Governorate that drives them to resort to the directorates of combatting violence against women; And that communication technology, the increase in population density, also the lack of institutions for psychological and social counseling services are among the driving factors for the continuation of patterns of violence against women in Sulaymaniyah Governorate.
Keywords: violence; violence against women; physical violence